2005
DOI: 10.1507/endocrj.52.1
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin and its Related Peptide

Abstract: MORE than 100 years have passed since Riva-Rocci [1] modified the sphygmograph by Marey [2], Mahomed [3] and Von Basch [4] to make conventional blood pressure measurements possible. Two years after the method was established, existence of hypertensive agents, now known as renin, was reported [5]. Since then laboratory investigations as well as clinical and epidemiological studies in hypertension research have been advancing at an exponential rate [6]. Since the 1950s, several circulation-regulating peptides, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 84 publications
1
11
0
2
Order By: Relevance
“…The inflammatory cytokines TNF-α, IL-1β, and bacterial endotoxin strongly stimulate the synthesis and secretion of AM [16,39]. It is speculated that the elevation in AM levels may be a protective mechanism to counteract cardiovascular disorders under such conditions [37]. In the current study, we also show that the upregulation of AM occurs after sepsis, jaundice as well as jaundice plus sepsis in rats.…”
Section: Discussionsupporting
confidence: 71%
“…The inflammatory cytokines TNF-α, IL-1β, and bacterial endotoxin strongly stimulate the synthesis and secretion of AM [16,39]. It is speculated that the elevation in AM levels may be a protective mechanism to counteract cardiovascular disorders under such conditions [37]. In the current study, we also show that the upregulation of AM occurs after sepsis, jaundice as well as jaundice plus sepsis in rats.…”
Section: Discussionsupporting
confidence: 71%
“…In this study, we also found that circulating levels of AM increased significantly at 24 hours after MCAO. The elevation in AM levels may be a protective mechanism to counteract cardiovascular disorders under disease conditions (33). However, the regulation of AM activity was largely unknown until the discovery of its novel binding protein, AMBP-1 (12).…”
Section: S E P T E M B E R -O C T O B E R 2 0 1 1 a M / A M B P -1 mentioning
confidence: 99%
“…However, hypoxia per se stimulates xanthine oxidase and NADPH oxidase, resulting in the increased production of oxidative stress (57). The pathogenic role of oxidative stress under hypoxic conditions was further emphasized by studies on the pulmonary vasculature using adrenomedullin, a potent antioxidant (58,59) that inhibits angiotensin II-induced oxidative stress (60). Chronic hypoxia was shown to induce pulmonary vascular remodeling, which was associated with an increased production of oxidative stress as measured by electron spin resonance and immunostaining of 3-nitrotyrosine.…”
Section: Oxidative Stressmentioning
confidence: 99%